2013
DOI: 10.1007/s11010-013-1897-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of microRNA-141 expression and its tumor suppressor function in human pancreatic ductal adenocarcinoma

Abstract: Increasing evidence shows that dysregulation of microRNAs is correlated with tumor development. This study was performed to determine the expression of miR-141 and investigate its clinical significance in pancreatic ductal adenocarcinoma (PDAC). Taqman quantitative RT-PCR was used to detect miR-141 expressions in 94 PDAC tissues and 16 nontumorous pancreatic tissues. Correlations between miR-141 expression and clinicopathologic features and prognosis of patients were statistically analyzed. The effects of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Studies have shown that expressions of miR-23 and miR-27 were upregulated during the normal development of retinal blood vessels and in response to laser-induced choroidal neovascularization (31). Clusters of miR-143/miR-145 are located in VSMCs, and deletion of these clusters can affect VSMC contractility and blood pressure (7,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that expressions of miR-23 and miR-27 were upregulated during the normal development of retinal blood vessels and in response to laser-induced choroidal neovascularization (31). Clusters of miR-143/miR-145 are located in VSMCs, and deletion of these clusters can affect VSMC contractility and blood pressure (7,25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of various miRNAs has been observed in the regulation of vascular function (1,31). For example, miR-145 participates in the regulation of VSMC contractility, and removal of miR-145 reduces the increase in systolic pressure in response to angiotensin II (1).…”
mentioning
confidence: 99%
“…Emerging evidence suggested that specific miRNA profiles were capable of distinguishing malignant and non-malignant tissues [128], raising the feasibility of miRNAs in early detection of cancer, prognosis informing, and treatment response monitoring. It was reported that the expression level of miR-141 in PDAC tissues was significantly lower than that in corresponding nontumorous tissues [90]. Downregulation of miR-141 correlated with poorer pT and pN status, advanced clinical stage, lymphatic invasion, and shorter overall survival, suggesting that miR-141 was an independent prognostic factor for PDAC patients.…”
Section: Mir-141 In Cancer Diagnosis and Prognosismentioning
confidence: 92%
“…More importantly, overexpression of YAP1 could rescue not only the downregulation of YAP1 but also the growth inhibition and caspase-3-dependent apoptosis enhancement in PANC-1 cells induced by miR-141 upregulation [90]. YAP1 was first identified by virtue of its ability to associate with the SH3 domain of Yes-and Srcprotein-tyrosine kinases [91].…”
Section: Mir-141 and Apoptosismentioning
confidence: 99%
“…Title and abstract assessment identified 37 manuscripts appropriate for evaluation of prognostic miRNA biomarkers in PDAC and full text articles were obtained for these. On careful review of study methodologies, 19 reports were excluded (Additional file 1: Table S1), of which 13 were studies focusing on a miRNA not investigated by a second study and therefore a pooled analysis would not be possible [19][20][21][22][23][24][25][26][27][28][29][30][31]. The details for the other 6 excluded studies can be seen in Additional file 2: Supplementary Results.…”
Section: Excluded Studiesmentioning
confidence: 99%